Initial transfusion intensity predicts survival in myelodysplastic syndrome. Issue 10 (October 2014) - Chan, Lap Shu Alan; Shapiro, Roman; Buckstein, Rena; Lin, Yulia; Callum, Jeannie; Chodirker, Lisa; Lee, Christina D.; Prica, Anca; Lam, Adam; Mamedov, Alexandre; Wells, Richard A.
Abstract We evaluated 52 patients with myelodysplastic syndrome (MDS) who had received at least one red blood cell (RBC) transfusion. In the 4-week period following the first transfusion, 24 patients (group 1) required no transfusion, while 28 (group 2) required transfusion of two or more units of RBCs. Survival was greater in group 1 (440 weeks vs. 167 weeks, p < 0.01), even when only international prognostic scoring system (IPSS) low and intermediate-1 risk patients were analyzed (median overall survival 491 vs. 170 weeks, p < 0.05), independent of age, IPSS and progression to acute myeloid leukemia (AML). The intensity of transfusion required in the first few weeks after the first transfusion predicts disease severity and correlates with survival.